Prognostic indices predictive of short-term disease-free survival of breast carcinoma patients receiving primary surgical treatment in Sri Lanka - Harshima Disvini Wijesinghe; Poobalasingham Thuvarakan; Anandi Samarasekera; Menaka Dilani S. Lokuhetty (Wolters Kluwer Medknow Publications, 2018)
Background: Breast carcinoma (BCa) is the commonest malignancy among women worldwide and in Sri Lanka. Several prognostic indices are described for BCa. Aims: To assess clinicopathological features and prognostic indices derived from routine clinical, histopathological and immunohistochemical (IHC) data, in a cohort of patients undergoing primary surgery for BCa and to determine their prognostic impact on short-term disease free survival. Setting and Design: This is a bidirectional cohort study of 208 women undergoing primary surgery for BCa at the National Hospital of Sri Lanka, from 2012-2014, excluding post-neoadjuvant chemotherapy cases. Material and Methods: Clinical details, tumor size and nodal status were obtained from histopathology reports. Histopathology and estrogen/progesterone receptor and HER2 status were reviewed. Molecular subtype based on IHC was determined. Nodal ratio (number of positive nodes/total number retrieved) and Nottingham prognostic index were calculated. Follow up information was obtained by patient interviews and record review. Statistical Analysis: Data was analyzed by univariate and multivariate Cox regression using SPSS19.0. Results: Mean follow-up duration was 27.16 months (0.5-52 months, s = 9.35 months). 174 (82.9%) remained disease free with 19 (9%) deaths. Thirteen (6.2%) survived with metastasis and 4 (1.9%) with recurrences. On univariate Cox regression, tumor, nodal and TNM stages, nodal ratio and lymphovascular invasion (LVI) were predictive of disease free survival (DFS) (P = 0.001, P = 0.021, P = 0.022, P = 0.002, P = 0.018). On multivariate analysis TNM stage and LVI were predictive of DFS. Conclusion: TNM stage and LVI were the most important predictors of short-term disease free survival in this study population, confirming that early detection of BCa at a lower stage has a significant impact on short-term outcomes.